Sosialisasi Pentingnya Sikap Hidup Hemat Dan Menabung Sejak Usia Dini Di Desa Latta - Roagave L. Toruan; Jusuf Leiwakabessy; Sherly Lewerissa; Valiand Sapulette; Audrey Leiwakabessy (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Considering that today's children mostly live with a consumerist attitude, it is necessary to provide education and introduction to the benefits of the value of money and manage finances by cultivating a frugal lifestyle and a love of saving from an early age. Educating them to avoid consumerist lifestyle behavior also aims to manage their own finances and can increase their comfort in the future. The main target of this activity is the community, especially children in Latta Village, Baguala District, Ambon City. This activity was attended by 25 children and 10 mothers in Latta Village. This activity program is implemented using the material presentation method. The main mission of socialization activities is to foster a frugal lifestyle, a hobby of saving from childhood for a more prosperous future, and children being able to differentiate between needs and wants.